Implikasi Penggunaan Alih Kode dalam Konten Tiktok terhadap Perencanaan dan Pembinaan Bahasa Indonesia di Era Digital (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The phenomenon of code switching in TikTok is increasingly widespread among young Indonesians. Mixing Indonesian with foreign languages, especially English, is a communication style that is considered expressive, modern and a digital identity. This study aims to identify forms of code switching in TikTok content and analyze its implications for planning and fostering Indonesian in the digital era. This study uses a qualitative descriptive approach with data in the form of screenshots of TikTok videos containing code switching. The results of the analysis show that the code switching that occurs is mixed and situational and has affective, stylistic functions, as a marker of social identity. Although it reflects language creativity, excessive use of code switching can have negative impacts such as shifting the structure of the Indonesian language, decreasing positive attitudes towards the national language, and hindering effective language development efforts. This study is expected to be an important input for educators, policy makers and the wider community in maintaining the sustainability and dignity of the Indonesian language in the digital era. Keywords: Code switching, TikTok, Language development, Indonesian, Digital Era